The SMFA program for quantum chemistry calculations on large molecules. (1st March 2019) - Kobayashi, Rika; Addicoat, Matthew A.; Gilbert, Andrew T.B.; Amos, Roger D.; Collins, Michael A.
Abstract : SMFA is a general program package for performing quantum chemistry calculations on large molecules, using an energy‐based fragmentation approach. The program can calculate electronic energies, energy gradients and second derivatives; perform geometry optimization; find first order saddle points (transition states); perform energy optimized scans along a user‐defined path; and evaluate various molecular properties. The program can use any of the following quantum chemistry packages: GAMESS(US), GAUSSIAN, NWChem and Q‐Chem. In addition, SMFA provides a number of utility programs that, inter alia, calculate vibrational frequencies and infrared spectra with isotopic substitutions, the electrostatic potential on the solvent‐accessible‐surface, and isodesmic and higher order near‐iso‐energetic reaction schemes. Calculations of the electronic energy and related properties can be carried out using a scheme that provides a computation time that is linearly dependent on the size of the molecule or, if the user has enough processing units available, in a walltime that is independent of the size of the molecule. This article is categorized under: Software > Quantum Chemistry Electronic Structure Theory > Ab Initio Electronic Structure Methods Structure and Mechanism > Computational Biochemistry and Biophysics Abstract : SMFA enables quantum chemistry calculations for proteins.